2011
DOI: 10.1371/journal.pone.0023720
|View full text |Cite
|
Sign up to set email alerts
|

Icaritin Shows Potent Anti-Leukemia Activity on Chronic Myeloid Leukemia In Vitro and In Vivo by Regulating MAPK/ERK/JNK and JAK2/STAT3 /AKT Signalings

Abstract: PurposeTo explore the effects of Icaritin on chronic myeloid leukemia (CML) cells and underlying mechanisms.MethodCML cells were incubated with various concentration of Icaritin for 48 hours, the cell proliferation was analyzed by MTT and the apoptosis was assessed with Annexin V and Hoechst 33258 staining. Cell hemoglobinization was determined. Western blotting was used to evaluate the expressions of MAPK/ERK/JNK signal pathway and Jak-2/Phorpho-Stat3/Phorsph-Akt network-related protein. NOD-SCID nude mice we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
78
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 35 publications
(39 reference statements)
0
78
0
Order By: Relevance
“…Icaritin caused sustained ERK1/2 activation and induced apoptosis in human endometrial cancer cells, and icaritin could also induce apoptosis in HepG2 cells via the JNK1 signaling pathway. Icaritin may be useful as an alternative therapeutic choice for imatinib-resistant forms of CML [23] .…”
Section: Wwwchinapharcom Wang Xf Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Icaritin caused sustained ERK1/2 activation and induced apoptosis in human endometrial cancer cells, and icaritin could also induce apoptosis in HepG2 cells via the JNK1 signaling pathway. Icaritin may be useful as an alternative therapeutic choice for imatinib-resistant forms of CML [23] .…”
Section: Wwwchinapharcom Wang Xf Et Almentioning
confidence: 99%
“…Based on the inhibitory effects of icaritin on the expression of MMP-2 and MMP-9, icaritin may have potential as a treatment for patients with advanced osteosarcoma. According to previous studies, the mechanisms underlying the antitumor activity of icaritin include the induction of apoptosis by multiple signaling pathways [5,6,20,23] . The caspase (cysteinyl aspartate specific protease) family is involved in apoptotic signal transduction and plays an important role in regulating apoptosis [37,38] .…”
Section: Wwwchinapharcom Wang Xf Et Almentioning
confidence: 99%
“…As already mentioned, STAT3 is a member of the JAK/STAT pathway that regulates CML (12). It also participates in the phosphatidylinositol 3-kinase/mammalian target of rapamycin/STAT3 pathway to regulate cell viability in breast cancer stem-like cells (29).…”
Section: Discussionmentioning
confidence: 97%
“…Signal transducers and activators of transcription (STAT) are important factors among these pathways, which are activated in blood cells from acute myeloid leukemia and CML (11). Among the STAT family members, STAT3 has been demonstrated to function in CML via the Janus activated kinase (JAK)/STAT pathway (12) and helps to mediate the anticancer activity of certain phytochemicals in the combination therapy of CML (13). Furthermore, its contribution to the regulation of the migration and viability of CML cells is indicated by molecular target studies (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that ERK and AKT signaling are the dominant pathway for icaritin to inhibit cancer cells growth in chronic myeloid leukemia, endometrial cancer renal cell carcinoma and breast cancer cells (15,17,18,35). Moreover, Li et al revealed that the apoptosis of human hepatoma was also induced via icariin treatment with ROS/JNK-dependent mitochondrial pathway (30).…”
Section: Discussionmentioning
confidence: 99%